2017
DOI: 10.1177/1755738017721939
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal cancer

Abstract: L aryngeal cancer is the most common form of head and neck cancer in the UK. The majority of cases are in people aged 60 years and over. Early diagnosis improves long-term outcomes and requires early recognition of significant symptoms and prompt referral. This article aims to provide an overview of the presenting features, investigation, management and follow-up of laryngeal cancer. The GP curriculum and laryngeal cancer Clinical module 3.15: Care of people with ENT, oral and facial problems states that GPs s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…These results could be ascribed to the fact that over half of patients were diagnosed with advanced cancer (stage III or IV); thus, early diagnosis is valuable for the treatments of laryngeal cancer [164]. Accumulating evidence suggests that ncRNAs play vital roles in the development of LSCC, which is the most common pathological type of laryngeal cancer [166], and could serve as diagnostic biomarkers. Evidence has shown that both miRNAs and lncRNAs were involved in LSCC [167][168][169][170], while studies on the circRNA involved in LSCC are rare.…”
Section: Circrnas In Lsccmentioning
confidence: 99%
“…These results could be ascribed to the fact that over half of patients were diagnosed with advanced cancer (stage III or IV); thus, early diagnosis is valuable for the treatments of laryngeal cancer [164]. Accumulating evidence suggests that ncRNAs play vital roles in the development of LSCC, which is the most common pathological type of laryngeal cancer [166], and could serve as diagnostic biomarkers. Evidence has shown that both miRNAs and lncRNAs were involved in LSCC [167][168][169][170], while studies on the circRNA involved in LSCC are rare.…”
Section: Circrnas In Lsccmentioning
confidence: 99%